2020
DOI: 10.1088/1757-899x/709/4/044113
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis and topology design optimization of load bearing elements of aircraft fuselage structure

Abstract: Aircraft total weight plays a major role in aircraft design which results in additional payloads and better performance. There are many ways to reduce weight of aircraft structures, for example, using composite materials.Composite materials such as CFRP offer significant weight reduction for aircraft. Weight reduction improves fuel efficiency of the aircraft which results cost of savings. Besides using these light materials structural design optimization is currently a valid methodology which is applied in adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Суть метода оптимизации топологии заключается в просчете программным комплексом Ansys наиболее выгодного способа размещения заданного количества материала, нагруженного известным набором сил, в ограниченном пространстве таким образом, чтобы обеспечивалась наименьшая масса конструкции при достаточной прочности и жесткости. Результаты работы, опубликованные в статье [26], показывают эффективность данного метода и снижение массы конструкции на 18,36 %.…”
Section: уточнение результатов использования новых конструкционных ма...unclassified
“…Суть метода оптимизации топологии заключается в просчете программным комплексом Ansys наиболее выгодного способа размещения заданного количества материала, нагруженного известным набором сил, в ограниченном пространстве таким образом, чтобы обеспечивалась наименьшая масса конструкции при достаточной прочности и жесткости. Результаты работы, опубликованные в статье [26], показывают эффективность данного метода и снижение массы конструкции на 18,36 %.…”
Section: уточнение результатов использования новых конструкционных ма...unclassified
“…Therefore, topological optimization proved to be a powerful tool to support designers in choosing the proper design process. Htet [23] optimized the topology of aircraft fuselage ribs using Ansys software. The results of this research showed that by using the topological optimization method, 18.36 percent of the original weight could be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Delamination simulation in composite laminates subjected to static or impact loads [19] has benefited greatly from CZM-based approaches. Some authors have subsequently expanded on these methods by include the Paris law within the cohesive constitutive model [20], thereby making it possible to account for degradation due to the cyclic load.…”
Section: Introductionmentioning
confidence: 99%